2018
DOI: 10.1144/sp469.18
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir architecture model of the Nieuwerkerk Formation (Early Cretaceous, West Netherlands Basin): diachronous development of sand-prone fluvial deposits

Abstract: The sand-prone fluvial Delft Sandstone Member of the Nieuwerkerk Formation is the main target for geothermal exploitation in the West Netherlands Basin. Uncertainty reduction in the modelling of permeability heterogeneity and connectivity of the sandstone reservoir units is of prime importance in the low-profit geothermal energy market. Lithostratigraphic correlation of the Delft Sandstone Member dates back to the 1970s, and considers the fluvial deposits as Valanginian (140–134 Ma) in age and synchronously de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The Upper Cretaceous sediments are therefore more homogeneous in thickness, wedging towards the basin margins (Fig. 2;Den Hartog Jager, 1996;Vondrak et al, 2018). The palaeo-coastline transgressed from the northwest boundary of the WNB in the Ryazanian to the northwest boundary of the Roer Valley Graben in Hauterivian times, which is reflected by increasingly marine sedimentation covering the terrestrial syn-tectonic strata (Den Hartog Jager, 1996;Herngreen and Wong, 2007;Jeremiah et al, 2010;Vejbbaek et al, 2010).…”
Section: Structural Geological Setting West Netherlands Basinmentioning
confidence: 98%
See 3 more Smart Citations
“…The Upper Cretaceous sediments are therefore more homogeneous in thickness, wedging towards the basin margins (Fig. 2;Den Hartog Jager, 1996;Vondrak et al, 2018). The palaeo-coastline transgressed from the northwest boundary of the WNB in the Ryazanian to the northwest boundary of the Roer Valley Graben in Hauterivian times, which is reflected by increasingly marine sedimentation covering the terrestrial syn-tectonic strata (Den Hartog Jager, 1996;Herngreen and Wong, 2007;Jeremiah et al, 2010;Vejbbaek et al, 2010).…”
Section: Structural Geological Setting West Netherlands Basinmentioning
confidence: 98%
“…Palynological and lithofacies analysis indicates that the siliciclastic Delft Sst Mbr succession formed in a relatively humid, lower-coastal-plain meandering-river depositional environment (Donselaar et al, 2015;Vondrak et al, 2018). Variability in net-togross and sandstone stacking patterns in the Nieuwerkerk Formation is the result of relative base-level fluctuations by differential movement along extensional faults in combination with rising sea level.…”
Section: Depositional Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Following on from hydrocarbon exploration experience, the Vlieland Sandstone Formation of the Rijnland Group was the primary target initially, with the deeper Schieland Group being a secondary target. However, geothermal wells drilled in synclines, contrary to anticlinal conventional oil and gas wells, found that the Schieland Group sandstones in the lows are thicker and have higher permeabilities than the pre-drill expectation (Willems et al 2017;Vondrak et al 2018). Presently, the Schieland Group sandstones, especially the Delft Sandstone Member, are the primary target for geothermal exploration with better reservoir characteristics and hotter than the overlying Vlieland Sandstone Formation sandstones.…”
Section: Future Trends and Developmentsmentioning
confidence: 99%